Reading speed, prosody, and comprehension results - Recio-Pineda, Sara Recio (2019)
The impact that the theory of automaticity has traditionally had on the explanation of reader development, together with the rise of concern that schoolchildren should acquire greater reading fluency, has caused a proliferation of studies that focus their attention on the speed of the readers. In general, however, these works have forgotten to interpret how reading prosody affects comprehension. The purpose of this paper is to explain how the variables of speed and prosody affect comprehension on a sample of 72 primary school students. A quantitative correlational method is used for this. The results point out that it is the prosody (and not the duration of the reading) what affects the quality of understanding in reading.